2023
DOI: 10.3390/nu15030571
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Lead and Cadmium Levels, and Serum Lipids with Subclinical Arteriosclerosis: Evidence from Taiwan

Abstract: Background: Exposure to lead and cadmium has been linked to changes in lipid metabolism and the development of arteriosclerosis, but the role of lipoprotein profiles in this relationship is not well understood, including the potential role of novel lipid biomarkers. Methods: In this study, we enrolled 736 young Taiwanese subjects aged 12 to 30 years to assess the correlation between urine levels of lead and cadmium, lipoprotein profiles, and carotid intima-media thickness (CIMT). Results: Higher levels of lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Moreover, simultaneous exposure to low doses of Pb and Cd may lead to cumulative cellular damage through shared molecular pathways. Previous animal studies and epidemiological research have proposed that these metals may exert synergistic effects on diverse health indicators, including lipid metabolism, biomarkers of oxidative stress, renal function, and blood pressure [3,[41][42][43]. In our prior investigation, we also found that the combined exposure to Pb and Cd might result in synergistic impacts on apoptotic microparticles [12].…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, simultaneous exposure to low doses of Pb and Cd may lead to cumulative cellular damage through shared molecular pathways. Previous animal studies and epidemiological research have proposed that these metals may exert synergistic effects on diverse health indicators, including lipid metabolism, biomarkers of oxidative stress, renal function, and blood pressure [3,[41][42][43]. In our prior investigation, we also found that the combined exposure to Pb and Cd might result in synergistic impacts on apoptotic microparticles [12].…”
Section: Discussionmentioning
confidence: 56%
“…The use of prebiotics represents a potential strategy for mitigating cadmium toxicity (Tinkov et al, 2018 ). This discovery unveils novel therapeutic targets and insights for treating cadmium-induced disorders, necessitating further investigation into the underlying mechanisms (Lin C. Y. et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis demonstrated that elevated Cd was correlated with increased TC levels (OR = 1.48, 95% CI: 1.10–2.01), increased LDL-C levels (OR = 1.31, 95% CI 0.99–1.73), and decreased HDL-C levels (OR = 1.96, 95% CI: 1.09–3.55) [ 41 ]. Several large-scale research studies have concluded that high Cd exposure increases the risk of dyslipidemia [ 33 , 42 ]. Most studies on the mechanism of Cd altering lipid metabolism have consistently shown that Cd interferes with the body’s antioxidant system.…”
Section: Discussionmentioning
confidence: 99%